Catalytic methods for the synthesis of 1,3-disubstituted bicyclo[1.1.1]pentanes - Shire, BR (2022)
Bicyclo[1.1.1]pentanes (BCPs) have emerged as useful bioisosteres for arenes in medicinal chemistry, demonstrating improved pharmacokinetic properties compared to the parent drugs. However, many syntheses still require the use of harsh conditions that are unsuitable for industrial applications. This thesis describes the development of new catalytic methodologies for the synthesis of 1,3-disubstituted BCPs, under mild conditions. Chapter 2 describes a photoredox-catalysed atom transfer radical addition between (hetero)aryl iodides and tricyclo[1.1.1.01,3]pentane (TCP), accessing 1-iodo-3-aryl-BCPs in a mild and efficient manner, and representing the first photoredox catalysed functionalisation of C–C σ bonds. Chapter 3 describes the iron-catalysed Kumada cross-coupling between (hetero)aryl Grignard reagents and 1-iodo-3-substituted BCPs. This established the first general cross-coupling in which BCPs act as the electrophilic cross-coupling component, as well as the first example of a Kumada cross-coupling of tertiary iodides. Chapter 4 describes the investigation of a copper-catalysed borylation of 1-iodo3-substituted BCPs and their subsequent oxidation to access BCP alcohols, representing the first conversion of BCP iodides to BCP alcohols without the need for tert-butyl lithium.